2018
DOI: 10.4067/s0718-58392018000100096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation with cracked wheat or high moisture corn on milk fatty acid composition of grazing dairy cows

Abstract: In Chile, high moisture corn (Zea mays L. [HMC]) has been included mainly in diets for grazing dairy cows on pastures with high crude protein, and is an alternative that improves nutrients supply and rumen synchrony between energy and protein provided by the diet. In addition, supplementation with HMC results in an increase of fatty acids (FA) in milk, desirable for human health. The aim of this study was to evaluate the effect of herbage allowance (HA) and type of supplement on milk FA composition in grazing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…In this study, feeding HMEC resulted in lower concentrations of SFA and higher concentrations of MUFA. Previous literature has shown that feeding HMEC helps cows consume polyunsaturated fatty acid (PUFA) precursors, leading to an increase in the content of PUFA in the milk [4], which similar with the present findings. This difference in fatty acid content between steam-flaked corn and HMEC, along with the combined effect of the rumen environment and different rations, could have influenced rumen biohydrogenation and, subsequently, the fatty acid content of the milk.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, feeding HMEC resulted in lower concentrations of SFA and higher concentrations of MUFA. Previous literature has shown that feeding HMEC helps cows consume polyunsaturated fatty acid (PUFA) precursors, leading to an increase in the content of PUFA in the milk [4], which similar with the present findings. This difference in fatty acid content between steam-flaked corn and HMEC, along with the combined effect of the rumen environment and different rations, could have influenced rumen biohydrogenation and, subsequently, the fatty acid content of the milk.…”
Section: Discussionsupporting
confidence: 92%
“…Milk production is a paramount indicator used to evaluate the performance of dairy cows, and it is influenced by various factors, with ration nutrition being one of the most significant [ 13 ]. Rojas-Garduño et al [ 4 ] found that feeding HMC (3.5 kg DM/cow/d) to dairy cows led to a significantly increased milk production of 2.3 kg/d. In the present study, the milk yield significantly increased in the 50% HMEC group and the 100% HMEC group by 0.81 kg and 1.18 kg, respectively, which similar with previous research findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbage DM intake was estimated, indirectly, once during each measurement period from animal performance results (15,16) as follows:…”
Section: Estimation Of Voluntary Intakementioning
confidence: 99%
“…The manipulation of FA profile of ruminant milk through changes in diets has been the subject of several studies, since milk fat contains numerous bioactive compounds with potential beneficial effects on human health. In addition, certain diets may induce the ruminal formation of specific FAs (e.g., conjugated linoleic acid , which inhibits mammary lipogenesis, with a consequent reduction in milk fat content (Garduño et al, 2018).…”
Section: Introductionmentioning
confidence: 99%